ANALYSIS ON THE EFFECT OF CURRENT RATIO, CASHFLOW FROM OPERATION TO DEBT, FIRM SIZE AND RETURN ON EQUITY ON STOCK RETURN - Rochim Rochim; Nunung Ghoniyah2 (UNISSULA, 2017)
This research is to learn some financial finance factor that can be used as a short prediction tool of return of investment decision in the form of stock. The object of research used in this study is a company incorporated in the Jakarta Stock Exchange during research periode 2012-2016. The variables studied were Profitability and Solvency. The analysis technique used in this research is linear regression. This research is done by quantitative method to the company’s financial statements listed in Jakarta Stock Exchange during period 2012-2016. Total sample of research is 35 company, which determined by purposive sampling method. Hypothesis testing method was conducted using t-test different test and linear regression. The results of this study indicate that there is a positive influence between Current Ration (CR), Cash Flow from Operation to Debt (CFOD), Firm Size, Return on Equity (ROE) to stock returns listed in Indonesia Stock Exchange during 2012 -2016.Keywords: Current Ration (CR), Cash Flow from Operation to Debt (CFOD), Firm Size, Return on Equity (ROE)